Conflict and Conflict Management in Organizations - Aris Teguh Hidayat; Muhammad Yamin; Susanti (Jurnal Kesehatan, 2025)
Introduction: In running an organization cannot be separated from the conflict in line with the change of plans and goals to be achieved by the organization. Good conflict resolution arrangements are required for conflict management to be implemented and conflict can be a functional conflict and have a positive impact on the organization. Method: This study uses an observational approach to the situation in a private organization in Indonesia. The author conducted observations during 2024 and analyzed the conflict management carried out in the organization. Results: Longstanding and rising conflicts and poor management of conflicts can lead to a decrease in the performance of the organization itself. Nurses as health care professionals sometimes have a different perspective with other health teams to provide quality care to patients. Conclusion: Conflicts in nursing that can be completed can result in better teamwork, productivity, and patient care. While non-functional nursing conflicts can lead to job dissatisfaction and decreased quality of services provided and ultimately impact on patients.